Looking in the mirror for the first time after facial burns: a retrospective mixed methods study - Shepherd, L.; Tattersall, H; Buchanan, Heather (Elsevier, 2014)
Appearance-related concerns are common following burns. However, there is minimal research that has specifically investigated patients' reactions when they looked in the mirror for the first time following facial burns. The current study aimed to investigate patients' reactions and factors associated with distress. Burns patients (n=35) who had sustained facial injuries completed a questionnaire which examined their reactions when looking in the mirror for the first time. Data were collected between April and July 2013. Participants had sustained their burns 12 months prior to participating, on average (ranging from one to 24 months). Forty-seven percent (n=16) of patients were worried about looking for the first time, 55% (n=19) were concerned about what they would see, and 42% (n=14) held negative mental images about what their faces looked like before they looked. Twenty-seven percent (n=9) of patients initially avoided looking, 38% (n=13) tried to 'read' others' reactions to them to try to gauge what they looked like, and 73% (n=25) believed that it was important for them to look. Mean ratings suggested that patients found the experience moderately distressing. Patients most often found the experience less distressing compared to their expectations. Distress was related to feeling less prepared, more worried and increased negative mental images prior to looking. In conclusion, patients' reactions to looking in the mirror for the first time vary. Adequately preparing patients and investigating their expectations beforehand is crucial. The findings have a number of important implications for practice.